2018
DOI: 10.1101/257709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A bacterial growth law out of steady-state

Abstract: SummaryBacterial growth depends on numerous reactions, and yet follows surprisingly simple laws that inspired biologists for decades. Growth laws until now primarily dealt with steady-state exponential growth in constant conditions. However, bacteria in nature often face fluctuating environments, with nutritional upshifts and downshifts. We therefore ask whether there are growth laws that apply to changing environments. We derive a law for strong upshifts using an optimal resource-allocation model that was pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 50 publications
(75 reference statements)
5
35
0
Order By: Relevance
“…Yet we observed differences at the genomic level that are consistent with recently proposed models, which predict that competitive advantage of bacteria under changing environmental condition is achieved by reserve capacity of ribosomes and transporters. Accordingly, sub-saturation allows bacteria to rapidly adapt in fluctuating environments by producing new ribosomes and high affinity transporters for optimal growth (54,55). We also observed that the disturbed period was significantly enriched in secretion system, which are used to deliver a variety of different proteins, including bacterial toxins and degradative enzymes such as proteases and lipases (56).…”
Section: Discussionmentioning
confidence: 79%
“…Yet we observed differences at the genomic level that are consistent with recently proposed models, which predict that competitive advantage of bacteria under changing environmental condition is achieved by reserve capacity of ribosomes and transporters. Accordingly, sub-saturation allows bacteria to rapidly adapt in fluctuating environments by producing new ribosomes and high affinity transporters for optimal growth (54,55). We also observed that the disturbed period was significantly enriched in secretion system, which are used to deliver a variety of different proteins, including bacterial toxins and degradative enzymes such as proteases and lipases (56).…”
Section: Discussionmentioning
confidence: 79%
“…However, recent work suggests that ribosomes are actually in excess, and that only a fraction are active, especially under non-exponential growth (Dai et al, 2016; Li et al, 2018). This excess would be particularly useful for the exit from quiescence, since the ability to transition to maximal protein synthesis as quickly as possible would provide a clear selective advantage (Korem Kohanim et al, 2018; Remigi et al, 2019). From this perspective, a reversible process such as the competitive binding of an inhibitor such as (p)ppGpp to a translational GTPase would facilitate the necessary down-regulation of protein synthesis to minimize energy consumption without impairing an optimal response to growth-permissive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ribosome synthesis is the single most energy consuming process in cells, preventing ribosome degradation, even when protein synthesis levels are low, would be evolutionarily favorable (6). In addition, a readily available, excess store of ribosomes under nutrient limitation would facilitate rapid resumption of growth when nutrients become available (43). The ability to transition to maximal protein synthesis as quickly as possible imparts a clear selective advantage for cells with higher ribosomal content (44, 45).…”
Section: Discussionmentioning
confidence: 99%